ECOLOGICAL BURDEN OF LARGE CITIES AND HYGIENIC CHANGES IN BIOLOGICAL MARKERS OF URBAN POPULATIONS - Raximov Baxodir; Sultonov Erkin; Baxtiyorov Bekzodjon; Najimov Nuriddin (Bright Mind Publishing, 2025)
The rapid expansion of large urban centers has heightened ecological pressures that significantly influence the biological markers of exposed populations, creating complex hygienic challenges that affect public health at molecular, physiological, and systemic levels. As urban environments experience intensified anthropogenic activities, including industrial emissions, vehicle exhaust, waste accumulation, reduced green spaces, and altered microclimates, residents are increasingly exposed to pollutants, toxicants, bioaerosols, noise, and psychosocial stressors, all of which contribute to measurable changes in biological markers associated with hygiene, inflammation, oxidative stress, immune function, endocrine regulation, and metabolic balance.
Keywords: Urban Ecology, Biological Markers, Hygienic Indicators, Ecological Burden, Oxidative Stress, Inflammation, Air Pollution, Urban Health, Biomonitoring.